Pengaruh Media Short Story Terhadap Kemampuan Kognitif Anak Kelompok B - Dunggio, Tiarahikma R.; Tine, Nurhayati; Sutisna, Icam (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2024)
This study aimed to improve the cognitive abilities of children in group B. The design of this research is a pre-experimental one group pretest-posttes design. The research subjects were twenty children selected through purposive sampling. It can be proven by the results of the pre-test (before the experiment) amounted to 17.6, and the post-test (after the experiment) amounted to 21.9 The test results obtained tcount = 5.92417962, ttable value at = 0.05; dk = n-1 (20-1 = 29) obtained = 1.729. Thus, tcount is greater than ttable (tcount = 5.92417962; ttable = 1.729,). Based on the test criteria, Ha is accepted if tcount ≥ ttable at = 0.05; n-1; therefore, the alternative hypothesis or Ha can be accepted. All in all, it can be stated that there is an effect of the short story method on children's cognitive abilities. Short stories that are packaged in short and concise form make it easier for children to focus and comprehend information.